2021
DOI: 10.1021/acs.jpcb.1c00325
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Photoinduced Electron Transfer and Resonance Energy Transfer in an Example of Substituted Cytochrome c–Quantum Dot Systems

Abstract: Colloidal quantum dots (QDs) are nanoparticles that are able to photoreduce redox proteins by electron transfer (ET). QDs are also able to transfer energy by resonance energy transfer (RET). Here, we address the question of the competition between these two routes of QDs’ excitation quenching, using cadmium telluride QDs and cytochrome c (CytC) or its metal-substituted derivatives. We used both oxidized and reduced versions of native CytC, as well as fluorescent, nonreducible Zn(II)CytC, Sn(II)CytC, and metal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…[ 20 ] When the positively charged Cyt c is mixed with the negatively charged GSH‐AuNCs, GSH‐AuNCs‐Cyt c nanobioconjugates may be formed through electrostatic interactions. This may induce fluorescence quenching due to electron transfer from GSH‐AuNCs to the heme cofactor of Cyt c. [ 21 ] It has been suggested that thiol groups and sulfur donor ligands (such as thiolates) can specifically bind to iron of Cyt c (Fe‐S). [ 22 ] The coordination of GSH sulfur with Cyt c iron facilitates electron transfer between GSH‐AuNCs and Cyt c. On the other hand, the absorption spectrum of Cyt c ranges from 300 to 650 nm with two absorption peaks at 409 and 528 nm due to the heme group of Cyt c protein (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] When the positively charged Cyt c is mixed with the negatively charged GSH‐AuNCs, GSH‐AuNCs‐Cyt c nanobioconjugates may be formed through electrostatic interactions. This may induce fluorescence quenching due to electron transfer from GSH‐AuNCs to the heme cofactor of Cyt c. [ 21 ] It has been suggested that thiol groups and sulfur donor ligands (such as thiolates) can specifically bind to iron of Cyt c (Fe‐S). [ 22 ] The coordination of GSH sulfur with Cyt c iron facilitates electron transfer between GSH‐AuNCs and Cyt c. On the other hand, the absorption spectrum of Cyt c ranges from 300 to 650 nm with two absorption peaks at 409 and 528 nm due to the heme group of Cyt c protein (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The two fluorescence emission peaks of the double QDs-ssDNA were located at 535 and 648 nm (Figure S1A). The double QDs-ssDNA could adsorb onto nanoCoTPyP via electrostatic interaction, π–π stacking, and hydrogen bonding, , leading to fluorescence quenching due to the fluorescence resonance energy transfer (FRET) and photoinduced electron transfer (PET). ,, As shown in Figure S1B, the UV–vis absorption spectra of nanoCoTPyP overlapped with the fluorescence emission spectrum of the double QDs-ssDNA, which was beneficial for the FRET processes. However, in the presence of target DNAs, target DNAs and ssDNA hybridized specifically to form more stable double-stranded DNA (dsDNA).…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches for qualitative as well as quantitative analysis of these bioanalytes have been developed, mainly based on electroanalytical techniques, , high-performance liquid chromatography (HPLC), , capillary electrophoresis separation, immunoassays based on derivatization with fluorescent/phosphorescent reagents, spectrophotometric methods, etc. , Unfortunately, all of these methods require either expensive reagents or equipment or skilled manpower to ensure reproducibility. In this context, much attention is being paid to the development of simple and cheap fluorescent probes, without compromising selectivity and sensitivity. Nanoparticles have been proven to be an efficient substitute for organic fluorophores, particularly for developing emission “turn on/off” sensors. Among various nanoparticles, quantum dots (QDs) are of particular interest in developing novel biosensors owing to their unique properties such as broad absorption band, emission in the visible region, photostability, etc. Moreover, the potential of QDs to transfer electrons or holes to biologically important molecules, interacting covalently or noncovalently with their surface, can be used to tune the QD emission intensity and thus generate charge transfer-based emission “on/off” signaling. …”
Section: Introductionmentioning
confidence: 99%